Analisis Risiko Berbasis ISO 31000 Pada Usaha Laundry: Studi Kasus Garsela - Tini Kartini; Yesi Amelia; Amira Muthi Ghassani; Anggi Mahmuddin; Alfiana Alfiana (Indonesia Economic Journal, 2026)
This study analyzes the implementation of ISO 31000–based risk management at Garsela Laundry, a micro, small, and medium enterprise (MSME) operating in the laundry service sector. The research aims to identify, analyze, evaluate, and formulate appropriate risk treatment strategies to support business sustainability and service quality. A qualitative case study approach was employed using in-depth interviews with the business owner, field observations, and document analysis. The risk identification process revealed 26 risks classified into six categories: operational, human resources, marketing, market, financial, and legal risks. Risk analysis using a 5×5 likelihood and impact matrix indicated several high-level risks, including clothing damage or stains, intense business competition, unstable income, increasing operational costs, and customer complaints. Risk treatment focused on high and medium risks through the development of standard operating procedures, improvement of employee discipline and skills, service quality enhancement, cost efficiency, and simple marketing strategies. The findings indicate that systematic implementation of ISO 31000 can minimize risk impacts, improve customer satisfaction, and strengthen the sustainability of laundry MSMEs.